2016
DOI: 10.18632/oncotarget.v7i44
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…found that PDL1 expression was associated with a prolonged OS in Extranodal Natural Killer/T-cell Lymphoma (ENKTCL) ( 17 ) and breast cancer ( 26 , 27 ). However, PDL1 expression was associated with shorter OS in pancreatic cancer, hepatocellular carcinoma and gastric cancer ( 26 , 28 ), and no association was observed between PDL1 expression and survival in patients with EOC ( 8 , 24 ). Our study showed an expression of PDL1 in 48.1% of HGSOC associated with an advanced stage and not correlated to 2-year OS in HGSOC.…”
Section: Discussionmentioning
confidence: 99%
“…found that PDL1 expression was associated with a prolonged OS in Extranodal Natural Killer/T-cell Lymphoma (ENKTCL) ( 17 ) and breast cancer ( 26 , 27 ). However, PDL1 expression was associated with shorter OS in pancreatic cancer, hepatocellular carcinoma and gastric cancer ( 26 , 28 ), and no association was observed between PDL1 expression and survival in patients with EOC ( 8 , 24 ). Our study showed an expression of PDL1 in 48.1% of HGSOC associated with an advanced stage and not correlated to 2-year OS in HGSOC.…”
Section: Discussionmentioning
confidence: 99%
“…These biomarkers include neutrophils, monocytes, lymphocytes, hemoglobin (HGB), lactate dehydrogenase (LDH), and other hematological biomarkers. 6,7 However, few studies have conducted a comprehensive discussion of these hematological biomarkers. Hence, the value of these markers in determining the prognosis or the survival rate after CRC surgery should be further evaluated.…”
Section: Introductionmentioning
confidence: 99%